Lassen und Tun: kulturphilosophische Debatten zum Verhältnis von Gabe und kulturellen Praktiken - Hobuß, Steffi; Tams, Nicola (Edition Moderne Postmoderne, 2014)
Theories of performativity and numerous cultural studies rudiments of philosophical thought in culture - such as that of Wittgenstein, Austin, or Butler - highlight the role of taking action within symbolic cultural practices. Passive shades of acting, as are currently inherent to donation, easily disappear from view. In this volume, phenomenological and constructivist perspectives on donation are brought together for the first time in order to invoke the unavailability of donation as a corrective to a perspective concentrated exclusively on active actions.